Isothiocyanate-Functionalized Bifunctional Chelates and fac-[M(I)(CO)(3)](+) (M = Re, (99m)Tc) Complexes for Targeting uPAR in Prostate Cancer - Kasten, Benjamin B. (Bioconjug Chem, 2015)
Developing new strategies to rapidly incorporate the fac-[M(I)(CO)(3)](+) (M = Re, (99m)Tc) core into biological targeting vectors in radiopharmaceuticals continues to expand as molecules become more complex and as efforts to minimize nonspecific binding increase. This work examines a novel isothiocyanate-functionalized bifunctional chelate based on 2,2′-dipicolylamine (DPA) specifically designed for complexing the fac-[M(I)(CO)(3)](+) core. Two strategies (postlabeling and prelabeling) were explored using the isothiocyanate-functionalized DPA to determine the effectiveness of assembly on the overall yield and purity of the complex with amine containing biomolecules. A model amino acid (lysine) examined (1) amine conjugation of isothiocyanate-functionalized DPA followed by complexation with fac-[M(I)(CO)(3)](+) (postlabeling) and (2) complexation of fac-[M(I)(CO)(3)](+) with isothiocyanate-functionalized DPA followed by amine conjugation (prelabeling). Conducted with stable Re and radioactive (99m)Tc analogs, both strategies formed the product in good to excellent yields under macroscopic and radiotracer concentrations. A synthetic peptide (AE105) which targets an emerging biomarker in CaP prognosis, urokinase-type plasminogen activator receptor (uPAR), was also explored using the isothiocyanate-functionalized DPA strategy. In vitro PC-3 (uPAR+) cell uptake assays with the (99m)Tc-labeled peptide (8a) showed 4.2 ± 0.5% uptake at 4 h. In a murine model bearing PC-3 tumor xenografts, in vivo biodistribution of 8a led to favorable tumor uptake (3.7 ± 0.7% ID/g) at 4 h p.i. with relatively low accumulation (<2% ID/g) in normal organs not associated with normal peptide excretion. These results illustrate the promise of the isothiocyanate-functionalized approach for labeling amine containing biological targeting vectors with fac-[M(I)(CO)(3)](+).